A market framework for grid balancing support through imbalances trading. (March 2021) - Lago, Jesus; Poplavskaya, Ksenia; Suryanarayana, Gowri; De Schutter, Bart
Abstract: To correct grid imbalances and avoid grid failures, the transmission system operator (TSO) deploys balancing reserves and settles these imbalances by penalizing the market actors that caused them. In several countries, it is forbidden to influence the grid imbalances in order to let the TSO retain full control of grid regulation. In this paper, we argue that this approach is not optimal as market actors that trade imbalances under the supervision of the TSO can help balancing the grid more efficiently. For instance, some systems such as solar farms cannot participate in the standard balancing market but do have economic incentives to help regulate the grid by trading with imbalances. Based on this argument, we propose a new market framework where any market actor is allowed to trade with imbalances. We show that, using the new market mechanism, the TSO can keep full control of the grid balance while decreasing the balancing cost. This is of primary importance as: 1) novel approaches to reduce grid imbalances are needed as, while renewable sources are generally not used for grid balancing, the increasing integration of renewable energy sources creates higher imbalances. 2) While long-term storage of energy is key in the energy transition, it needs to become an attractive investment to ensure its widespread use; as we show, the proposed market can guarantee that. Based on a real case study, we show that the new market can provide 10–20% of the total balancing energy needed and reduce the balancing costs. Highlights: Market framework that allows renewable sources to provide balancing services. The new market lowers balancing costs and increases integration of renewable sources. The proposed framework enhances the economic viability of seasonal storage systems. The new market ensures competitive trading practices.